2022
DOI: 10.21203/rs.3.rs-1352040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lactic acid from vaginal microbiota enhances cervicovaginal epithelial barrier integrity by promoting tight junction protein expression

Abstract: Background: Women with a cervicovaginal microbiota dominated by Lactobacillus spp. are at reduced risk of acquiring sexually transmitted infections including HIV but the biological mechanisms involved remain poorly defined. Here we performed metaproteomics on vaginal swab samples from young South African women (n=113) and transcriptomics analysis of cervicovaginal epithelial cell cultures to examine the ability of lactic acid, a metabolite produced by cervicovaginal lactobacilli, to modulate genital epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(71 reference statements)
0
2
1
Order By: Relevance
“…Several recent studies have shown that lactic acid was capable of promoting the integrity of epithelial barrier function. For instance, Delgado-Diaz et al revealed efficacy with respect to cervicovaginal epithelial barrier integrity [49], and Huang et al revealed that lactate provided protection against gastric mucosal injury and the inflammatory response induced by ethanol administration by upregulating TJ proteins [50] On the other hand, it is unlikely that lactic acid contributed to the function of LP06CC2 in the present study, as the LLB diet promoted ZO-1 expression but elevation of fecal lactic acid was not observed.…”
Section: Discussioncontrasting
confidence: 49%
“…Several recent studies have shown that lactic acid was capable of promoting the integrity of epithelial barrier function. For instance, Delgado-Diaz et al revealed efficacy with respect to cervicovaginal epithelial barrier integrity [49], and Huang et al revealed that lactate provided protection against gastric mucosal injury and the inflammatory response induced by ethanol administration by upregulating TJ proteins [50] On the other hand, it is unlikely that lactic acid contributed to the function of LP06CC2 in the present study, as the LLB diet promoted ZO-1 expression but elevation of fecal lactic acid was not observed.…”
Section: Discussioncontrasting
confidence: 49%
“…Likewise, a protective role of lactobacilli in the vaginal environment has been attributed to the decrease in vaginal pH through the production of L-and D-lactic acid via glycogen and glucose metabolism (22,(36)(37)(38). Given the significant reductions in tst expression demonstrated in the luciferase assays (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is a symbiotic relationship between L. crispatus and the cervical mucosal epithelium; L. crispatus can secrete lactic acid to increase the expression of cervical epithelial barrier proteins claudin1 and claudin4 to some extent, and its supernatant can also alleviate the increase in miRNA expression induced by pathogenic bacteria (Delgado-Diaz et al, 2022;Anton et al, 2017;Anton et al, 2018). Conversely, the supernatants of pathogenic bacteria, including Mobiluncus mulieris and Gardnerella vaginalis, increased the permeability of cervical cells and the expression of miR-143 and miR-145, thereby reducing the proliferation of epithelial cells and promoting the breakdown of the cervical epithelial barrier (Anton et al, 2017;Anton et al, 2018).…”
Section: Effects Of the Interactions Between The Microbiome And The A...mentioning
confidence: 99%
“…In a balanced female reproductive tract microecology, the mucosa, optimal pH, and appropriate immune response provide favorable conditions for the colonization of the tissue-resident microbiome (Wira et al, 2005;Anderson et al, 2014). Cervicovaginal Lactobacillus strengthen the epithelial barrier to prevent the invasion of pathogenic bacteria, thereby reducing reproductive tract infections and maintaining reproductive tract health (Delgado-Diaz et al, 2022;Anton et al, 2017;Anton et al, 2018). Endometrial tissue-resident microbiome, such as Lactobacillus and Bacteroides, compete with pathogenic bacteria for ecological niches and may regulate maternal-fetal immune tolerance, which is conducive to protecting the upper reproductive tract from pathogenic bacteria and embryo implantation (Moreno et al, 2016;Kim et al, 2019;Mazmanian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%